Ketidakpastian Pengaturan Risalah RUPS Telekonferensi Berlandaskan Prinsip Kehati-Hatian Bagi Notaris - Mahdum Islah Mumpuni (Officium Notarium, 2023)
The involvement of a notary in the implementation of a GMS by teleconference is in the preparation of the minutes of the deed. The legal basis for preparing the minutes of the GMS by teleconference deed is Law no. 40 of 2007 on Limited Liability Companies has legal uncertainty which certainly can endanger the principle of prudence held by notaries. In article 77 paragraph (4) is explained that the minutes of the GMS by teleconference must be signed by all GMS participants, whereas article 90 paragraphs (1) and (2) does not require the minutes to be signed by all GMS participants and it is not required that they be made with a notarial deed, these provisions creates legal uncertainty for notaries. The formulation of the problem in this research is: whether the arrangement of the minutes of the GMS by teleconference fulfills the principle of legal certainty and how to implement the principle of notarial prudence in preparing the minutes of the deed of the Closed PT GMS by teleconference. The research used is normative law with statutory and conceptual approaches. The results of the research concluded that the arrangement of the minutes of the GMS by teleconference does not fulfill the element of legal certainty because there are multiple interpretations between article 77 paragraph (4) and article 90 paragraph (1) and paragraph (2) and a notary is legally bound to the application of the precautionary principle in reviewing regulations and the making of legal productsKey Word: Legal uncertainty, precautionary principle, teleconference GMS AbstrakLatar Keterlibatan notaris dalam pelaksanaan RUPS telekonferensi ada pada penyusunan risalah aktanya. Dasar hukum penyusunan risalah akta RUPS telekonferensi yaitu Undang-Undang No. 40 Tahun 2007 tentang Perseroan Terbatas memiliki ketidakpastian hukum yang tentunya dapat membahayakan prinsip kehati-hatian yang dipegang oleh notaris. Dalam Pasal 77 ayat (4) dijelaskan bahwa risalah RUPS telekonferensi harus di tandatangani seluruh peserta RUPS sedangkan pada Pasal 90 ayat (1) dan (2) tidak mewajibkan risalah untuk ditandatangani oleh seluruh peserta RUPS dan tidak disyaratkan apabila dibuat dengan akta notaris, ketentuan tersebut menimbulkan ketidakpastian hukum bagi notaris. Rumusan masalah dalam penelitian ini yaitu : apakah pengaturan risalah RUPS secara telekonferensi sudah memenuhi prinisp kepastian hukum dan bagaimana implementasi prinsip kehati-hatian notaris dalam penyusunan risalah akta RUPS PT Tertutup secara telekonferensi. Penelitian yang digunakan adalah hukum normatif dengan pendekatan perundang-undangan dan konseptual. Hasil penelitian menyimpulkan bahwa pengaturan risalah RUPS secara telekonferensi belum memenuhi unsur kepastian hukum karena timbul multitafsir antar Pasal 77 ayat (4) dengan Pasal 90 ayat (1) dan ayat (2) dan sebagai seorang notaris dalam menerapkan prinsip kehat-hatian diperlukan ketelitian dalam mengkaji peraturan dalam membuat produk hukum.Kata-kata Kunci: Ketidakpastian hukum, prinsip kehati-hatian, RUPS telekonferensi